Students' Self-Confidence and the Production of Fillers in Speaking English - Yanti, Tri Septi Setia Darma; Humaira, Zalfa Hana; Rosmayati, Elin; Darsih, Endang (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to explore the relationship between students’ self-confidence and the use of fillers in English speaking skills. Fillers such as “um”, “uh”, “like”, and “you know” are linguistic elements that often appear in oral communication, especially when the speaker is hesitant or needs time to think. This study used a qualitative approach with a case study design. Data were collected through direct observation in class presentation activities and semi-structured interviews with ten students of the English Education Study Program at Kuningan University. The results showed that all participants used fillers in varying frequencies, with a tendency to increase when they felt insecure, nervous, or when experiencing a lack of ideas. Non-verbal indicators such as eye contact, intonation, and body language showed that students with lower self-confidence used fillers more often. Although most were aware of the presence of fillers in their speech, only a few had concrete strategies to reduce them. These findings indicate that low self-confidence is closely related to the increasing use of fillers. This study is expected to contribute to the development of English-speaking learning strategies that focus not only on linguistic aspects but also on students’ psychological readiness.